Beyond local boundaries: unraveling the spatiality of entrepreneurial ecosystems - Schäfer, Susann; Fischer, Bruno Brandão; Schaeffer, Paola Rücker; Balestrin, Alsones (Journal of Business Venturing Insights, 2024)
The underlying rationale of Entrepreneurial Ecosystems (EE) interactions is essentially attached to geographical space. So far, literature remains largely focused on a shortsighted notion of EE as ‘insular’ systems. In this article we address the spatial dynamics of two ecosystems based on the inflow of venture capital over the last three decades. Drawing from the cases of Tokyo and Bangalore, our key insight is that the EE configurations cannot be properly understood without a clear assessment of its spatial features. i.e., the geographical scope of connections that compose EE. As it turns out, EE present heterogeneous spatialities - and these evolve along different trajectories. This, we believe, is a key missing piece of the EE theoretical puzzle.